Optimizing Merdeka Curriculum in West Aceh: Challenges and Opportunities in Education - Zikriati, Zikriati; Arani, Samsuar (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2024)
This study evaluates the implementation of the Independent Curriculum in West Aceh District and its significant implications for local education policies. Through comprehensive regional-level analysis, this study explores its potential impact on enhancing educational quality. This research uses survey methods, interviews, and document analysis to understand better the dynamics of the Independent Curriculum's implementation in West Aceh. The findings indicate positive outcomes such as curriculum flexibility, freedom in teaching methodologies, and responsiveness to local conditions, which align with the principles of freedom-based learning approaches. This is consistent with literature emphasizing the importance of allowing teachers and schools to design a curriculum more relevant to local needs and student characteristics. However, challenges such as resource limitations, understanding of educational freedom, low community participation, and resistance to change reflect implementation issues identified in the literature. Consequently, implementing the Independent Curriculum necessitates careful strategies to overcome these obstacles and ensure its effectiveness. Improvement in teacher quality through further professional development aligns with research affirming that well-trained teachers positively impact student learning outcomes. These findings contribute to understanding the Independent Curriculum's implementation locally, serving as a valuable reference for policymakers and educational practitioners in similar regions.